2018
DOI: 10.3233/bpl-180076
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mouse Models as Tools for Understanding How Increased Cognitive and Physical Stimulation Can Improve Cognition in Alzheimer’s Disease

Abstract: Cognitive decline appears as a core feature of dementia, of which the most prevalent form, Alzheimer’s disease (AD) affects more than 45 million people worldwide. There is no cure, and therapeutic options remain limited. A number of modifiable lifestyle factors have been identified that contribute to cognitive decline in dementia. Sedentary lifestyle has emerged as a major modifier and accordingly, boosting mental and physical activity may represent a method to prevent decline in dementia. Beneficial effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 193 publications
5
25
0
Order By: Relevance
“…The trends toward improved cognitive function (Fig 2), the clear increase in neurogenesis, as well as the lack of a notable impact on brain inflammation and amyloid deposition (Fig. 3 and 4) that we observed are consistent with previous studies of the impact of exercise on mouse models of AD [72]. We next sought to determine if these exercise-mediated changes were correlated with an increase in brain blood flow, perhaps linked to a decrease in the incidence of non-flowing capillaries.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The trends toward improved cognitive function (Fig 2), the clear increase in neurogenesis, as well as the lack of a notable impact on brain inflammation and amyloid deposition (Fig. 3 and 4) that we observed are consistent with previous studies of the impact of exercise on mouse models of AD [72]. We next sought to determine if these exercise-mediated changes were correlated with an increase in brain blood flow, perhaps linked to a decrease in the incidence of non-flowing capillaries.…”
Section: Resultssupporting
confidence: 92%
“…We found performance in the object replacement task in 12-month-old APP/PS1 mice was markedly improved by three months of voluntary wheel running, as compared to sedentary controls, while no improvements were detected in the novel object recognition task and Y-maze tasks. This exercise-related improvement in performance on some memory-related tasks but not on others is consistent with similarly mixed impacts of exercise in previous studies of memory function in mouse models of AD [72] and in AD patients [78]. While a variety of brain regions are likely involved in each of these memory tasks, it has been shown that memory of an object’ s spatial location (evaluated with object replacement task) is highly dependent on hippocampal regions, while memory of an object’ s intrinsic characteristics (evaluated with novel object task) also involves significant contributions from other brain regions, such as the temporal lobe [79-81].…”
Section: Discussionsupporting
confidence: 90%
“…Multiple studies show that lifestyle interventions such as environmental enrichment and exercise rescue spatial learning and memory in WM task [38,39]. However, some studies have also reported that exercise does not improve the spatial learning and memory in AD mice [40]. Rather, environmental enrichment improves the WM performance of AD mice [41].…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise intervention shows an improvement or rescue of cognitive dysfunction in AD mouse models [40] with one exception [41]. Measures such as active lifestyle, education, or physical exercise help to rescue the cognitive function in elderly [40]. Similarly, earlier report from Nun Study points possibility of the positive association between the genetic risk factor such as 4 allele of apolipoprotein E (APOE 4) and dementia [51].…”
Section: Cognitive Reserve and Cognitive Training Via Wm Taskmentioning
confidence: 98%
See 1 more Smart Citation